MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI AKTIVITAS MENGGAMBAR DAN MEWARNAI - Masganti Sitorus; Rahma Adlya Zahra; Rama Yuspika Sari; Sarah Rizky Aulia; Salsabila Siregar (STKIP Subang, 2023)
This study aims to investigate the effect of drawing and coloring activities on improving early childhood cognitive abilities. Drawing and coloring activities are considered as fun and creative activities for children, but they also have the potential to improve their cognitive abilities. The research method used was an experiment with a control group. Fifty children aged 4-6 years were randomly selected and divided into two groups, namely the experimental group which did drawing and coloring activities, and the control group which did not. The experimental group was given a series of drawing and coloring tasks designed to engage various cognitive aspects such as color recognition, hand-eye coordination, problem solving, and spatial understanding. Meanwhile, the control group was involved in daily routine activities without any special intervention. Before and after the intervention, both groups were given cognitive ability tests which included tests of memory, problem solving, and understanding of basic concepts. The results showed that the group of children who did drawing and coloring activities experienced a significant increase in cognitive abilities compared to the control group. They showed better improvements in memory tests, problem solving, and understanding basic concepts. In addition, children in the experimental group also showed an increase in their creativity and imagination. These findings indicate that drawing and coloring activities can be an effective method of improving early childhood cognitive abilities. Therefore, it is suggested that these activities be integrated in the early childhood education curriculum to enrich their learning experience and promote optimal cognitive development.